A Case Report on Acotiamide’s Role in De-Prescribing PPI – An Offbeat Approach - Vishnupriya, V (International Journal of Human and Health Sciences (IJHHS), 2024)
Proton pump Inhibitors (PPI) are the commonest over the counter medications which are abused. Its prescribed even for minor gastric events and patients tend to take it for indefinite periods.PPI abuse can lead to wide range of toxic events like nephritis, osteoporosis, cardiac events, Clostridium infections, vitamin malabsorption. There are not many reports on management of pantaprazole abuse. Acotiamide is a drug which enhances acetylcholine release from enteric neurons through muscarinic receptor antagonism and acetylcholinesterase (AchE) inhibition, thereby enhancing gastric emptying and gastric accommodation. Here I am presenting a 36-year-old female with daily pantaprazole or omeprazole 40mg intake. She came for quitting the PPIs and was successfully managed with acotiamide and gradual tapering of the PPI. International Journal of Human and Health Sciences Vol. 08 No. 02 Apr’24 Page: 212-214